Ekstraksi Kitosan dari Limbah Cangkang Udang sebagai Adsorben Ion Logam Cu pada Air Kolong Timah Bangka - Herman Aldila (PROMINE, 2020)
This study aims to analyze the effect of NaOH concentration on deacetylation step on the chitosan adsorption for Cu metal ions in Bangka tin kolong’s water. Extraction of chitosan was carried out in four steps: deproteinization, demineralization, decolorization and deacetylation of chitin. The effect of NaOH concentration on deacetylation process was studied. The results shown that the increase of NaOH concentration from 20% to 60%, the chitosan DD increased. The diffusion rate of OH- causes increment of OH- attack to the amino group thus realizing the effective deacetylation of chitin. The metal content of Cu in this study reached 0.32 ppm. Adsorption of chitosan on cu metal ions reduced the dissolved levels reaching an average of 99.67% from the initial content. The content of the hydroxyl group in chitosan causes the forming reaction of hydroxide compounds from dissolved Cu metal ions. The Cu hydroxide compound will separately form and form a precipitate. The greater the deacetylation degree value lead increase of hydroxyl group content and causing the increase of Cu metal ions adsorption.